miR-23a impairs bone differentiation in osteosarcoma via down-regulation of GJA1 - Gindin, Yevgeniy; Jiang, Yuan; Francis, Princy; Walker, Robert L.; Abaan, Ogan D.; Zhu, Yuelin J.; Meltzer, Paul S. (Frontiers in Genetics, 2015)
Osteosarcoma is the most common type of bone cancer in children and adolescents. Impaired differentiation of osteoblast cells is a distinguishing feature of this aggressive disease. As improvements in survival outcomes have largely plateaued, better understanding of the bone differentiation program may provide new treatment approaches. The miRNA cluster miR-23a∼27a∼24-2, particularly miR-23a, has been shown to interact with genes important for bone development. However, global changes in gene expression associated with functional gain of this cluster have not been fully explored. To better understand the relationship between miR-23a expression and bone cell differentiation, we carried out a large-scale gene expression analysis in HOS cells. Experimental results demonstrate that over-expression of miR-23a delays differentiation in this system. Downstream bioinformatic analysis identified miR-23a target gene connexin-43 (Cx43/GJA1), a mediator of intercellular signaling critical to osteoblast development, as acutely affected by miR-23a levels. Connexin-43 is up-regulated in the course of HOS cell differentiation and is down-regulated in cells transfected with miR-23a. Analysis of gene expression data, housed at Gene Expression Omnibus, reveals that Cx43 is consistently up-regulated during osteoblast differentiation. Suppression of Cx43 mRNA by miR-23a was confirmed in vitro using a luciferase reporter assay. This work demonstrates novel interactions between microRNA expression, intercellular signaling and bone differentiation in osteosarcoma.